Morphological, infrared, and ionic conductivity studies of poly(ethylene oxide)-49% poly(methyl methacrylate) grafted natural rubber-lithium perchlorate salt based solid polymer electrolytes - Ahmad A. (2023)
The potential of poly(ethylene oxide) (PEO) and 49% poly(methyl methacrylate) grafted natural rubber (MG49) as a polymer host in solid polymer electrolytes (SPE) was explored for electrochemical applications. PEO-MG49 SPEs with various weight percentages of lithium perchlorate salt (LiClO 4) was prepared with the solution casting technique. Characterization by scanning electron microscopy, Fourier transform infrared spectroscopy, and impedance spectroscopy was done to investigate the effect of LiClO 4 on the morphological properties, chemical interaction, and ionic conductivity behavior of PEO-MG49. Scanning electron microscopy analysis showed that the surface morphology of the sample underwent a change from rough to smooth with the addition of lithium salts. Infrared analysis showed that the interaction occurred in the polymer host between the oxygen atom from the ether group (C-O-C) and the Li + cation from doping salts. The ionic conductivity value increased with the addition of salts because of the increase in charge carrier up to the optimum value. The highest ionic conductivity obtained was 8.0 - 10 -6 S/cm at 15 wt % LiClO 4. 2011 Wiley Periodicals, Inc.